Trace amounts of antibiotic altered metabolomic and microbial profiles of weaned pigs infected with a pathogenic E. coli - Kwangwook Kim; Cynthia Jinno; Peng Ji; Yanhong Liu (Journal of Animal Science and Biotechnology, 2022)
Abstract Background Our previous study has shown that supplementation of trace amounts of antibiotic exacerbated the detrimental effects of enterotoxigenic E. coli (ETEC) infection and delayed the recovery of pigs that may be associated with modified metabolites and metabolic pathways. Therefore, the objective of this study was to explore the impacts of trace levels of antibiotic (carbadox) on host metabolic profiles and colon microbiota of weaned pigs experimentally infected with ETEC F18. Results The multivariate analysis highlighted a distinct metabolomic profile of serum and colon digesta between trace amounts of antibiotic (TRA; 0.5 mg/kg carbadox) and label-recommended dose antibiotic (REC; 50 mg/kg carbadox) on d 5 post-inoculation (PI). The relative abundance of metabolomic markers of amino acids, carbohydrates, and purine metabolism were significantly differentiated between the TRA and REC groups (q < 0.2). In addition, pigs in REC group had the highest (P < 0.05) relative abundance of Lactobacillaceae and tended to have increased (P < 0.10) relative abundance of Lachnospiraceae in the colon digesta on d 5 PI. On d 11 PI, pigs in REC had greater (P < 0.05) relative abundance of Clostridiaceae compared with other groups, whereas had reduced (P < 0.05) relative abundance of Prevotellaceae than pigs in control group. Conclusions Trace amounts of antibiotic resulted in differential metabolites and metabolic pathways that may be associated with its slow responses against ETEC F18 infection. The altered gut microbiota profiles by label-recommended dose antibiotic may contribute to the promotion of disease resistance in weaned pigs.